Negative regulation of signal transducer and activator of transcription-3 signalling cascade by lupeol inhibits growth and induces apoptosis in hepatocellular carcinoma cells - Siveen, K.; Nguyen, A.; Lee, J.; Li, F.; Singh, S.; Kumar, Alan Prem; Low, G.; Jha, S.; Tergaonkar, V.; Ahn, K.; Sethi, G. (Nature Publishing Group, 2014)
Background: Constitutive activation of signal transducer and activator of transcription signalling 3 (STAT3) has been linked with survival, proliferation and angiogenesis in a wide variety of malignancies including hepatocellular carcinoma (HCC). Methods: We evaluated the effect of lupeol on STAT3 signalling cascade and its regulated functional responses in HCC cells. Results: Lupeol suppressed constitutive activation of STAT3 phosphorylation at tyrosine 705 residue effectively in a dose- and time-dependent manner. The phosphorylation of Janus-activated kinases (JAKs) 1 and 2 and Src was also suppressed by lupeol. Pervanadate treatment reversed the downregulation of phospho-STAT3 induced by lupeol, thereby indicating the involvement of a phosphatase. Indeed, we observed that treatment with lupeol increased the protein and mRNA levels of SHP-2, and silencing of SHP-2 abolished the inhibitory effects of lupeol on STAT3 activation. Treatment with lupeol also downregulated the expression of diverse STAT3-regulated genes and decreased the binding of STAT3 to VEGF promoter. Moreover, the proliferation of various HCC cells was significantly suppressed by lupeol, being associated with substantial induction of apoptosis. Depletion of SHP-2 reversed the observed antiproliferative and pro-apoptotic effects of lupeol. Conclusions: Lupeol exhibited its potential anticancer effects in HCC through the downregulation of STAT3-induced pro-survival signalling cascade.